The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0037-86822012000300017
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum infection in pregnant women attending antenatal care in Luanda, Angola

Abstract: Introduction: Malaria during pregnancy remains a serious public health problem. The aim of this study was to establish the prevalence and possible risk factors for malaria in pregnant women attending antenatal care at Augusto Ngangula Specialized General Hospital in Luanda, Angola. Methods: Pregnant women (679 total) who attended antenatal care from April to September 2008 were included in the study after signing informed consent. For each participant, the social-demographic profile and malaria and obstetric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
4
8
1
Order By: Relevance
“…This agrees with findings not only in areas of stable transmission of malaria [25],[33] but also in areas with unstable transmission [23],[34]. Anaemia was the main complication of malaria infection found in our study and remains the most frequent consequence of malaria during pregnancy irrespective of transmission level and pre-pregnancy level of malaria immunity [35].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with findings not only in areas of stable transmission of malaria [25],[33] but also in areas with unstable transmission [23],[34]. Anaemia was the main complication of malaria infection found in our study and remains the most frequent consequence of malaria during pregnancy irrespective of transmission level and pre-pregnancy level of malaria immunity [35].…”
Section: Discussionsupporting
confidence: 92%
“…In Mali, parity was significantly associated with malaria infection only when the analysis was not adjusted for age [21]. Other authors found no association between parity and malaria infection [19],[23],[25]. In the present study and as well as in that of Adam et al .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In India malaria cases decreased with an increasing monthly income [37]. This result contradicts findings in Indonesia that indicated that working participants were 1.2 times more likely to have malaria than those who were not [38]. This could be due to type of employment.…”
Section: Discussionmentioning
confidence: 95%
“…However, these successes are threatened by the emergence of artemisinin-resistant strains of Plasmodium falciparum from the Thai-Cambodian border 3 and Thai-Myanmar border 4 . Indeed, artemisinin resistance is a major threat to global health, particularly in low-and middle-income countries (LMICs), in which the disease burden is highest, substandard or counterfeit ACT compounds are widely available, and systems for the monitoring and containment of resistance are inadequate [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%